PROMOSI KESEHATAN DI SEKOLAH PADA REMAJA DALAM UPAYA PENCEGAHAN PENYAKIT HIV/AIDS DI KOTA DENAPASAR - N.K., Ekawati; Wulandari, L.P.L.; Lubis, D.; Purnama, S.G. (Buletin Udayana Mengabdi; Vol 11 No 2 (2012): Jurnal Udayana Mengabdi, 2012)
The highest group of HIVAIDS cases in Bali is the productive age group, where more transmission through sexual intercourse with multiple partners and low usage of condom use among injecting drug users. Focus of prevention and health promotion in schools is required. One effort is done through health promotion in schools aiming to improve students’ knowledge of HIV/AIDS and the dangers of HIV/AIDS. This Community Service deals with health promotion and prevention efforts against HIV/AIDS in adolescents. The methods used were Discussions and lectures with Leflet media, books about HIV/AIDS and foster. Participants’ knowledge of HIV/AIDS in terms of modes of transmission and prevention has been understood, but not all participants understood correctly as the understanding of HIV/AIDS, modes of transmission and means of prevention. Participants understand that all people affected by a range of HIV/AIDS. Vulnerability will be infected by the HIV/AIDS a deadly risk makes participants take action to prevent the discriminatory PLWHA such as away from the people affected by HIV/AIDS and PLWHA brought into rehabilitation. Health promotion for HIV/AIDS is indispensable to be held continuously.